CLINICAL VALUE OF REGULATORY AUTOANTIBODIES IN DEVELOPMENT OF NEUROINTOXICATION WITH METALLIC MERCURY VAPOURS - G. M. Bodienkova; E. V. Boklazhenko; E. V. Katamanova (Acta Biomedica Scientifica, 2012)
We studied the changes in content of the autoantibodies to the antigens from nervous tissue was performed in the employees contacting with, metallic mercury, in the patients with, the mercury intoxication, at the different stages of the pathological process. It was found that small increase of concentrations of the autoantibodies to the protein S-100 in the "practically" healthy employees may be considered, as the protective physiological mechanism.. Influence of the mercury on the employees' organisms promotes the change of autoimmune reactions that are characterized by the increase of content of antibodies to the brain-specific proteins in blood serum.. The decrease of the antibody levels in patients with chronic mercury intoxication, in remote period and the increase of severity of pathological process testifies to the dysregulation in the immune system.. It was determined, that the increase of autoantibodies to MAG was typical only for the patients with chronic mercury intoxication. (CMI), thereby, higher levels of autoantibodies were observed in the patients with more dominated cognitive disorders in comparison with the patients with more dominated asthenic disorders. In healthy employees and the ones of "risk group" concentrations of autoantibodies to MAG were at the level of control. Increased, levels of autoantibodies to MAG testify to the formation of neurodegenerative changes and. are one of the diagnostic criteria.